On the sociological approach to public finance - Sarah L. Quinn (economic sociology_the european electronic newsletter, 2020)
The sociological study of credit in political economies is a useful entry point for understanding what economic sociology can bring to the study of public finance. In this research note, I want to highlight one aspect of this, namely how a sociological focus on the political economy of credit enables an approach to public finance that is both critical and expansive.
Keywords: 300